Role of Aminotransferase IlvE in Production of Branched-Chain Fatty Acids by Lactococcus lactis subsp. lactis - Ganesan, Balasubramanian (American Society for Microbiology, 2004)
The objective of this study was to determine the role of a lactococcal branched-chain amino acid aminotransferase gene, ilvE, in the production of branched-chain fatty acids. Lactococcus lactis subsp. lactis LM0230 and an ilvE deletion mutant, JLS450, produced branched-chain fatty acids from amino and α-keto acids at levels above α-keto acid spontaneous degradation and the fatty acids' flavor thresholds. The deletion mutant produced the same amounts of branched-chain fatty acids from precursor amino acids as did the parent. This was not the case, however, for the production of branched-chain fatty acids from the corresponding precursor α-keto acids. The deletion mutant produced a set of fatty acids different from that produced by the parent. We concluded from these observations that ilvE plays a role in the specific type of fatty acids produced but has little influence on the total amount of fatty acids produced by lactococci.